Driving HIV-1 into a Vulnerable Corner by Taking Advantage of Viral Adaptation and Evolution - Harada, Shigeyoshi; Yoshimura, Kazuhisa (Frontiers in Microbiology, 2017)
Anti-retroviral therapy (ART) is crucial for controlling human immunodeficiency virus type-1 (HIV-1) infection. Recently, progress in identifying and characterizing highly potent broadly neutralizing antibodies has provided valuable templates for HIV-1 therapy and vaccine design. Nevertheless, HIV-1, like many RNA viruses, exhibits genetically diverse populations known as quasispecies. Evolution of quasispecies can occur rapidly in response to selective pressures, such as that exerted by ART and the immune system. Hence, rapid viral evolution leading to drug resistance and/or immune evasion is a significant barrier to the development of effective HIV-1 treatments and vaccines. Here, we describe our recent investigations into evolutionary pressure exerted by anti-retroviral drugs and monoclonal neutralizing antibodies (NAbs) on HIV-1 envelope sequences. We also discuss sensitivities of HIV-1 escape mutants to maraviroc, a CCR5 inhibitor, and HIV-1 sensitized to NAbs by small-molecule CD4-mimetic compounds. These studies help to develop an understanding of viral evolution and escape from both anti-retroviral drugs and the immune system, and also provide fundamental insights into the combined use of NAbs and entry inhibitors. These findings of the adaptation and evolution of HIV in response to drug and immune pressure will inform the development of more effective antiviral therapeutic strategies.